Pathogen Safety of Long-Term Treatments for Bleeding Disorders: (Un)Predictable Risks and Evolving Threats - Di Minno, Giovanni; Canaro, Mariana; Ironside, James W.; Navarro, David; Perno, Carlo F.; Tiede, Andreas; Guertler, Lutz (Seminars in Thrombosis and Hemostasis, 2013)
Substantial improvements in the safety of blood and plasma products for the management of bleeding disorders have been achieved in recent decades. This has led some clinicians to believe that the infectious threat is over and that inhibitor formation is the foremost complication of hemophilia therapy. On the contrary, elimination of all microbes from blood is difficult, potentially impossible, and there are always threats from emerging pathogens. The risk of infection transmission is also increasing due to greater exposure to products, increasing prophylaxis and high-dose regimens for immune tolerance, and longevity of hemophilia patients. Current products can be considered “reasonably safe,” but pathogen testing is not all-inclusive, and manufacturing and purification techniques are often not standardized. Although safer nonplasma-derived products are widely used, they are not available for all bleeding disorders, and so there is an ongoing need for plasma-derived products. This review will discuss the evolving risk from emerging pathogens in the context of the issues described. Reducing the risk from emerging infections requires global collaboration to devise ways to monitor and continue to improve blood safety.
Keywords: bleeding disorders; blood safety; emerging infectious agent(s)